Politics of Hadramis: Resources Mobilization Toward Local Election in Pekalongan, Indonesia - Efendi, David; Suswanta, Suswanta; Khakim, Muhammad Lukman (Universitas Muhammadiyah Yogyakarta, 2020)
This paper aims to explain how to do and by what manner hadramis politics succeed in gaining influence in the local election in Pekalongan. The power of Hadrami in this city can be observed from three periods of local election in which they become the winner for city Mayor. That achievement can be easily understood due to their dominant power in religion, economics, education, civil society organization (Al Isryad), and health institution. Hadramis gained many strategic positions and had a considerable effect on society. Traditionally, Arabs lineage is identically Al Irsyad, which was affiliated with Golkar since the New Order. Also, the role of socio-economic development has become a habitus to this Arab lineage since the 19thcentury. As a result, the influence of Hadrami clerics is so apparent. Therefore, the position of this Hadrami can mobilize voters quickly politically and psychologically. It became the most critical modality component to explain how Pierre Bourdieu's theory can be employed. By doing field research and doing a series of interviews in a qualitative approach, this paper aims to dig deeper to answer how the politics of Hadrami works. The findings are that the Hadrami community successfully combines modalities such as religious identity dominance, an enormous power in economic capital, social networks, and public service. Those capitals have transformed into political support toward electoral democracy. This opportunity is strongly influenced by social infrastructure as a well-established plural community. However, Hadramis itself is not a single and trustworthy entity in the political field to be so dynamic in reality toward a local election.